ChemInform Abstract: Synthesis, Structure and Inhibitory Activity of a Stereoisomer of Oseltamivir Carboxylate. Issue 26 (1st July 2014) - Sartori, Andrea; et al., et al.
Abstract The first total synthesis of 4‐epi‐oseltamivir carboxylate (I) is described.